RUMAH SINGGAH PASIEN KANKER PAYUDARA DENGAN PENDEKATAN KONSEP HEALING ENVIRONMENT DI KOTA SURAKARTA - Mandayaningrum, Emma Indira; Singgih, Edi Pramono; Yuliani, Sri (Universitas Sebelas Maret Surakarta, 2016)
The Background of the shelter house design for breast cancer patient using healing environment in Surakarta city is the increasing number of breast cancer patient in Surakarta city, uneven facility and infrastructure of breast cancer treatment in Indonesia, and there is no shelter house especially for breast cancer patient in Surakarta city. Therefore the aim of this design is to get a building design which can facilitate and serve the breast cancer patient’s activity and treatment. The building design considers healing environment concept in Surakarta city. The problem of the design is how to plan and design shelter house for breast cancer patient using healing environment concept in Surakarta city which can facilitate the activity for a certain time with a certain education system. The method that used is architecture planing method. The result is the building which consider healing environment concept in Surakarta city.